Developing Local MSMEs with Indonesian Socio-Culture Service Learning for Muria's Processed Parijoto Fruit - Ananingsih, Victoria Kristina; Putra, Yohanes Alan Sarsita; Pratiwi, Alberta Rika; Sumardi, Sumardi (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
The concept of entrepreneurship empowerment was explored in depth to highlight its multifaceted nature and its role in fostering economic growth and cultivating a positive community mindset, which in turn spurred the development of essential infrastructure contributing to community empowerment. Service Learning, as a strategy for community entrepreneurship empowerment in the Indonesian culture, was enacted through the collaboration of faculty and university students who were acknowledged for their capacity to deliver authentic learning experiences. It, thereby, facilitated the acquisition of both soft and hard skills. This initiative exemplified the coordinated efforts among universities, such as the local MSME (Micro, Small, and Medium Enterprises) Community of processed Parijoto fruit, and its various partners. The execution of this community service program, which was done in Muria, comprised six primary phases: surveying, conducting interviews, gathering data, preparing materials, engaging in focus group discussions, formulating action plans, and conducting evaluations and reflections. The outcomes encompassed the analysis of laboratory products, educational sessions, mentoring activities, and the creation of educational resources. While the assessment of processing parijoto fruit yielded positive impacts from the endeavor,  it was found to have a need to optimize support from businesses to sustain a conducive environment for MSMEs. Such entrepreneurship training initiatives have demonstrated efficacy in empowering communities and generating further prospects for individuals residing in rural areas.